Effects of Monetary Policy Shocks on Farm Prices and Exchange Rates in Korea. Issue 11 (2nd November 2017) - Kim, Jihae; Kim, Soyoung
ABSTRACT: The effects of monetary policy shocks on farm prices and exchange rates in Korea are empirically investigated by using vector auto-regression models with sign restrictions on impulse responses. The main empirical results are as follows. First, (contractionary) monetary policy shocks have significantly negative effects on real farm prices. Second, the SR effect on farm prices is significant but short-lived. The dynamic response of farm prices is consistent with the predictions of the "overshooting" model. Third, the effects of monetary policy shocks on farm prices are more significant than the effects of monetary policy shocks on exchange rates.